Modified PBT material for laser marking and preparation method thereof

Through the components and preparation methods of modified PBT materials, the problem of insufficient marking quality and flame retardant performance of PBT materials during laser marking is solved, and better marking effect and material performance are achieved.

CN119859389APending Publication Date: 2025-04-22JIANGYIN LONGSHAN SYNTHETIC MATERIAL
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411388345.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-08
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

The existing PBT materials have poor marking quality, blurred patterns, and insufficient flame retardant and mechanical properties when laser marking, resulting in the product being cracked or too brittle and hard.

Method used

Modified PBT materials are used, and the raw material components include end carboxy PBT resin, toughener, flame retardant, glass fiber, compatibility agent, laser marker, laser radium masterbatch and antioxidant. The compatibility and crosslinking of the material are improved through pretreatment and multiple mixing steps.

Benefits of technology

The marking quality and pattern clarity of laser marking are improved, the flame retardant, mechanical and oxidation resistance of the material are enhanced, and the requirements for the 750℃ hot wire contact material not to catch fire.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a modified PBT material for laser marking and a preparation method thereof, and relates to the technical field of engineering plastics. The modified PBT material for laser marking is prepared from the following raw material components in parts by weight: 40 to 50 parts by mass of carboxyl-terminated PBT resin, 5 to 8 parts by mass of a toughening agent, 15 to 25 parts by mass of a flame retardant, 20 to 30 parts by mass of glass fibers, 0.6 to 0.8 part by mass of a compatilizer, 0.5 to 1.5 parts by mass of a laser marking agent, 1 to 3 parts by mass of laser carving color master batch and 0.2 to 0.4 part by mass of an antioxidant, the terminal carboxyl group content of the terminal carboxyl group PBT resin is 20-30 mol / t; the toughening agent is obtained by modifying an ethylene-vinyl acetate copolymer with 4-vinyl phenylacetic acid; the flame retardant is prepared by compounding phenyl dichlorophosphine modified brominated epoxy resin and an MCA flame retardant according to a mass ratio of 16: (6-8); 2, 6-dimethylphenol is adopted as the antioxidant.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of engineering plastics, in particular to a modified PBT material for laser marking and a preparation method thereof. Background Art

[0002] Polybutylene terephthalate (PBT) is a thermoplastic with high crystallinity and fast crystallization characteristics. It is popular in laser marking applications due to its excellent processing performance. However, PBT has a relatively weak absorption capacity for lasers, which means that higher laser power and slower scanning speeds are often required to obtain clear marks during laser marking. Existing laser marking technology often encounters problems such as poor marking quality, blurred patterns, and yellowing of the marked area when processing PBT. In order to improve these problems, special laser marking masterbatches are usually added to PBT materials to improve their laser response performance.

[0003] In addition, PBT must meet the requirements of UL 94 V0 fire rating in the application and be able to remain non-combustible at a high temperature of 750°C. In order to achieve these performance indicators, halogen-free flame retardant systems are usually used to reinforce PBT materials. However, this halogen-free flame retardant system is more expensive and requires a larger addition amount than the bromine-containing flame retardant system, which may lead to a decrease in the mechanical properties of the material, which may cause the product to crack or become too brittle. In contrast, although the bromine-containing flame retardant system can reduce costs, it will only allow the material's glow-wire ignition temperature to reach a maximum of 725°C.

[0004] In view of the above problems, we have developed a modified PBT material specifically for laser marking, aiming to solve the above-mentioned technical challenges. Summary of the invention

[0005] In order to solve the existing technical problems, the present invention provides a modified PBT material for laser marking. The raw material components include, by weight: 40-50 parts by weight of terminal carboxyl PBT resin, 5-8 parts by weight of toughening agent, 15-25 parts by weight of flame retardant, 20-30 parts by weight of glass fiber, 0.6-0.8 parts by weight of compatibilizer, 0.5-1.5 parts by weight of laser marking agent, 1-3 parts by weight of laser laser engraving masterbatch, and 0.2-0.4 parts by weight of antioxidant.

[0006] Furthermore, the terminal carboxyl content of the terminal carboxyl PBT resin is 20-30 mol / t.

[0007] Furthermore, the toughening agent is obtained by modifying ethylene-vinyl acetate copolymer with 4-vinylphenylacetic acid.

[0008] Furthermore, the flame retardant is compounded with phenyl dichlorophosphine modified brominated epoxy resin and MCA flame retardant in a mass ratio of 16:6-8.

[0009] Furthermore, the antioxidant is 2,6-dimethylphenol.

[0010] Furthermore, the laser marking agent is obtained by mixing tin dioxide, mica, aluminum oxide, titanium dioxide and antimony pentoxide in a mass ratio of 3-5:5-8:4-6:2-3:3-5.

[0011] Furthermore, the compatibilizer is amide wax; The present invention also provides a method for preparing a modified PBT material for laser marking, and the preparation steps are as follows: (1) Ingredients: Weigh and prepare the ingredients according to the following raw material components and proportions: 40-50 parts by weight of carboxyl-terminated PBT resin, 5-7 parts by weight of toughening agent, 15-25 parts by weight of flame retardant, 20-30 parts by weight of glass fiber, 0.6-0.8 parts by weight of compatibilizer, 0.5-1.5 parts by weight of laser marking agent, 1-3 parts by weight of laser laser engraving masterbatch, and 0.2-0.4 parts by weight of antioxidant; (2) Pretreatment of carboxyl-terminated PBT resin: 40-50 parts by weight of carboxyl-terminated PBT resin, 12-15 parts by weight of benzyltrichloride, 0.01-0.02 parts by weight of ferric chloride, and 120-150 parts by weight of tetrachloromethane are mixed and stirred for 2-4 hours, and then heated at 65-78°C for 1 hour to obtain a pretreated PBT resin; benzoic acid and benzyltrichloride in the carboxyl-terminated PBT resin are co-heated to modify the carboxyl-terminated PBT resin so that the pretreated PBT resin contains benzoyl chloride; (3) Pretreatment of toughening agent: 5-7 parts by weight of toughening agent, 1.5-3.5 parts by weight of benzyltrichloride, 0.015-0.021 parts by weight of ferric chloride, 20-50 parts by weight of acetone, and 50-90 parts by weight of tetrachloromethane are mixed and stirred for 2-4 hours, and then heated at 65-78° C. for 1 hour to obtain a pretreated toughening agent; benzyltrichloride and toughening agent phenylacetic acid are co-heated to form phenylacetyl chloride in the toughening agent; (4) primary mixing: the pretreated toughening agent prepared in step (3), the antioxidant, 0.2-0.4 parts by weight of anhydrous aluminum chloride, and 50-90 parts by weight of 1,2-dichloroethane are mixed, stirred at 40° C. for 4-6 hours, and then quenched with an iced 1 mol / L HCl solution. The mixture obtained after quenching is extracted twice with dichloromethane, and after extraction, it is washed twice with deionized water, a 5% sodium bicarbonate aqueous solution, and a saturated NaCl solution, and then rotary evaporated to obtain a primary mixture; at this time, phenylacetyl chloride in the toughening agent reacts and grafts with the antioxidant 2,6-dimethylphenol to form 1-(4-hydroxy-3,5-dimethylbenzene)-2-acetophenone in the primary mixture; (5) Secondary mixing: the primary mixture, the flame retardant, 100-200 parts by mass of dichloromethane, 6-8 parts by mass of triethylamine, and 0.01 parts by mass of dimethylaminopyridine are mixed at 5°C, then the temperature is raised to 25°C and stirred for 3-5 hours, and the mixture is extracted twice with dichloromethane. After extraction, the mixture is washed twice with deionized water, a 5% sodium bicarbonate aqueous solution, and a saturated NaCl solution, and then rotary evaporated to obtain a secondary mixture; the phenyl dichlorophosphine in the flame retardant reacts with the hydroxyl group in the primary mixture to form diphenyl acetophenone phenyl phosphite in the secondary mixture; (6) Tertiary mixing: the secondary mixture, the pretreated PBT resin, 10-20 parts by weight of aluminum chloride, and 180-200 parts by weight of benzene are stirred and dispersed at 1200-1800 rpm for 10-30 min, then heated to 80° C., stirred and reacted for 1.8-2.2 h, then heated to 110° C., stirred and reacted at 1300-1700 rpm overnight until substantially no hydrogen chloride gas is generated, and then cooled to room temperature to obtain a tertiary mixture; the benzoyl chloride in the pretreated PBT resin reacts and grafts with the benzene ring in the secondary mixture to form benzophenone in the tertiary mixture; (7) Fourth mixing: The tertiary mixture, 20-30 parts by weight of glass fiber, 0.6-0.8 parts by weight of compatibilizer, 0.5-1.5 parts by weight of laser marking agent, and 1-3 parts by weight of laser laser engraving masterbatch are mixed evenly, and then blended and granulated in a twin-screw extruder. At the same time, the obtained composite material is injection molded in an injection molding machine to obtain a modified PBT material for laser marking.

[0012] Furthermore, the preparation method of the toughening agent is as follows: 50-70 parts by weight of pre-irradiated ethylene-vinyl acetate copolymer, 30-50 parts by weight of 4-vinylphenylacetic acid, 0.5 parts by weight of dispersant calcium hydroxyphosphate, 0.5 parts by weight of emulsifier sodium dodecylbenzene sulfonate, 0.09-0.15 parts by weight of initiator benzoyl peroxide, and 210-350 parts by weight of distilled water were mixed, stirred and reacted at 70-80° C. for 7-9 hours. After the reaction, the mixture was washed with acetone and deionized water for 2-4 times, filtered, and dried in a vacuum drying oven at 65° C. for 10-12 hours to obtain a toughening agent.

[0013] Furthermore, the preparation steps of the pre-irradiated ethylene-vinyl acetate copolymer are as follows: the ethylene-vinyl acetate copolymer is pre-irradiated with beta rays through a 120kW electron accelerator, and the irradiation conditions are: the transmission speed is set to 4.8m / min, the acceleration voltage is 3MeV, the beam length is 7.5cm, the scanning width is 1.2m, and the irradiation dose is 10kGy to obtain the pre-irradiated ethylene-vinyl acetate copolymer.

[0014] Furthermore, the preparation method of the phenyl dichlorophosphine modified brominated epoxy resin is as follows: After mixing the brominated epoxy resin, triethylamine and toluene, add dropwise a toluene solution of 66% by mass of phenyldichlorophosphine at -5-0°C while stirring, raise the temperature to 70-80°C after the addition is complete, and keep the temperature to react for 2-4 hours. After the reaction is completed, cool the mixture, filter out triethylamine hydrochloride, evaporate the filtrate under reduced pressure to remove the solvent and excess triethylamine, then recrystallize the mixture with acetonitrile, dry it, and seal it for storage to obtain a brominated epoxy resin modified with phenyldichlorophosphine; wherein the molar ratio of hydroxyl group, triethylamine and phenyldichlorophosphine in the brominated epoxy resin is 1:0.9-1.1:1-1.2, and the mass ratio of brominated epoxy resin to toluene is 1:3.2-3.4.

[0015] Furthermore, the temperatures of each section of the twin-screw extruder are: 200~210℃ in zone 1, 210~220℃ in zone 2, 220~230℃ in zone 3, 220~230℃ in zone 4, 220~230℃ in zone 5, 200~210℃ in zone 6, 200~210℃ in zone 7, 210~220℃ in zone 8, 230~250℃ in die head, and screw speed: 300r / min; The injection molding conditions: The temperatures of each section of the injection molding machine are: 250℃, 250℃, 250℃, 250℃, 230℃.

[0016] Compared with the prior art, the present invention has the following beneficial effects: The modified PBT material for laser marking of the present invention comprises raw material components: carboxyl-terminated PBT resin, toughening agent, flame retardant, glass fiber, compatibilizer, laser marking agent, laser laser carving masterbatch and antioxidant; the carboxyl-terminated PBT resin has a carboxyl-terminated content of 20-30 mol / t; the toughening agent is obtained by modifying ethylene-vinyl acetate copolymer with 4-vinylphenylacetic acid; the flame retardant is compounded by modifying brominated epoxy resin with phenyl dichlorophosphine and MCA flame retardant; and the antioxidant is 2,6-dimethylphenol.

[0017] Firstly, the toughening agent of the present invention adopts 4-vinylphenylacetic acid to modify ethylene-vinyl acetate copolymer, and polar groups are introduced into ethylene-vinyl acetate copolymer by grafting 4-vinylphenylacetic acid with ethylene-vinyl acetate copolymer, thereby increasing the compatibility of ethylene-vinyl acetate copolymer with carboxyl-terminated PBT resin, thereby enhancing the mechanical properties of the modified PBT material for laser marking.

[0018] Secondly, the flame retardant is obtained by compounding phenyl dichlorophosphine modified brominated epoxy resin and MCA flame retardant; wherein, part of the P-Cl groups in phenyl dichlorophosphine react and graft with the hydroxyl groups in the brominated epoxy resin to form phenyl monochlorophosphite derivatives, which synergize with the brominated epoxy resin and MCA flame retardant to enhance the flame retardant properties of the modified PBT material for laser marking; and the addition of MCA flame retardant not only has a flame retardant effect, but also can ensure a high glow wire.

[0019] Finally, when preparing the modified PBT material for laser marking, the carboxyl-terminated PBT resin and the toughening agent are first pretreated with benzyltrichloride to form benzoyl chloride and phenylacetyl chloride in the carboxyl-terminated PBT resin and the toughening agent, respectively; then the pretreated toughening agent and the antioxidant are mixed once, and the phenylacetyl chloride in the pretreated toughening agent reacts with the antioxidant 2,6-dimethylphenol to form 1-(4-hydroxy-3,5-dimethylbenzene)-2-acetophenone, which increases the compatibility between the antioxidant and the toughening agent. At high temperature, the acetone group in 1-(4-hydroxy-3,5-dimethylbenzene)-2-acetophenone removes a water molecule during thermal decomposition to form a triple bond. As the temperature further increases, an isomerization reaction occurs between the two benzene rings and the triple bond to form a terphenyl structure, which is finally converted into a carbon material with an aromatic structure of terphenyl through further condensed ring aromaticization. The flame retardant, mechanical properties and high glow wire of the modified PBT material for laser marking are increased in one step; then the primary mixture and the flame retardant are mixed for a second time, and the remaining P-Cl group of the phenyl dichlorophosphine in the flame retardant reacts with the hydroxyl group in the primary mixture to form dibenzoyl ketone phenyl phosphite in the secondary mixture, and the molecular chains of the brominated epoxy resin and the toughening agent are cross-linked together, thereby improving the flame retardant, antioxidant and mechanical properties of the modified PBT material for laser marking; then the secondary mixture and the pretreated PBT resin are mixed for a third time, and the benzoyl chloride in the pretreated PBT resin reacts and grafts with the benzene ring in the secondary mixture to form dibenzophenone, and the brominated epoxy resin, the toughening agent molecular chain and the PBT resin molecular chain are cross-linked together to form a highly cross-linked network structure, thereby further improving the mechanical properties and antioxidant properties of the modified PBT material for laser marking. DETAILED DESCRIPTION

[0020] The present invention is further described in detail below in conjunction with examples, but the following examples should not be construed as limiting the present invention.

[0021] The sources of some raw materials in the examples and comparative examples of the present invention are as follows: Carboxyl-terminated PBT resin: carboxyl-terminated content is 20~30 mol / t; Mica (grade CF-A3), Qingdao Yousuo Chemical Technology Co., Ltd.; The brominated epoxy resin used was EP-10000 from Shandong Tianyi Chemical Co., Ltd.; Glass fiber: T635B, Taishan Glass Fiber Co., Ltd. Laser engraving masterbatch uses black masterbatch RF2030C produced by Guangzhou Runfeng Chemical Co., Ltd., pigment carbon black, and carrier resin PBT; The compatibilizer is commercially available amide wax. Example 1

[0022] A method for preparing a modified PBT material for laser marking, the preparation steps are as follows: (1) Ingredients: Weigh and prepare the ingredients according to the following raw material components and proportions: 40 parts by mass of carboxyl-terminated PBT resin, 5 parts by mass of toughening agent, 15 parts by mass of flame retardant, 20 parts by mass of glass fiber, 0.6 parts by mass of compatibilizer, 0.5 parts by mass of laser marking agent, 1 part by mass of laser laser engraving masterbatch, and 0.2 parts by mass of antioxidant; (2) Pretreatment of carboxyl-terminated PBT resin: 40 parts by weight of carboxyl-terminated PBT resin, 12 parts by weight of benzyltrichloride, 0.01 parts by weight of ferric chloride, and 120 parts by weight of tetrachloromethane were mixed and stirred for 2 h, and then heated at 65 °C for 1 h to obtain a pretreated PBT resin; (3) Toughening agent pretreatment: 5 parts by weight of toughening agent, 1.5 parts by weight of benzyltrichloride, 0.015 parts by weight of ferric chloride, 20 parts by weight of acetone, and 50 parts by weight of tetrachloromethane were mixed and stirred for 2 hours, and then heated at 65° C. for 1 hour to obtain a pretreated toughening agent; (4) primary mixing: the pretreated toughening agent prepared in step (3), the antioxidant, 0.2 parts by mass of anhydrous aluminum chloride, and 50 parts by mass of 1,2-dichloroethane are mixed, stirred at 40° C. for 4 h, and then quenched with an ice-cold 1 mol / L HCl solution. The mixture obtained after quenching is extracted twice with dichloromethane. After extraction, it is washed twice with deionized water, a 5% sodium bicarbonate aqueous solution, and a saturated NaCl solution, and then rotary evaporated to obtain a primary mixture; (5) Secondary mixing: the primary mixture, flame retardant, 100 parts by mass of dichloromethane, 6 parts by mass of triethylamine, and 0.01 parts by mass of dimethylaminopyridine were mixed at 5°C, then heated to 25°C and stirred for 3 hours, extracted twice with dichloromethane, washed twice with deionized water, 5% sodium bicarbonate aqueous solution, and saturated NaCl solution after extraction, and then rotary evaporated to obtain a secondary mixture; (6) Tertiary mixing: The secondary mixture, the pretreated PBT resin, 10 parts by mass of aluminum chloride, and 180 parts by mass of benzene were stirred and dispersed at 1200 rpm for 10 min, then heated to 80° C. and stirred for reaction for 1.8 h, then heated to 110° C. and stirred at 1300 rpm for reaction overnight until substantially no hydrogen chloride gas was generated, and then cooled to room temperature to obtain a tertiary mixture; (7) Fourth mixing: The tertiary mixture, 20 parts by weight of glass fiber, 0.6 parts by weight of a compatibilizer, 0.5 parts by weight of a laser marking agent, and 1 part by weight of a laser engraving masterbatch are uniformly mixed, and then blended and granulated in a twin-screw extruder. At the same time, the obtained composite material is injection molded in an injection molding machine to obtain a modified PBT material for laser marking.

[0023] Furthermore, the preparation method of the toughening agent is as follows: 50 parts by mass of pre-irradiated ethylene-vinyl acetate copolymer, 30 parts by mass of 4-vinylphenylacetic acid, 0.5 parts by mass of dispersant calcium hydroxyphosphate, 0.5 parts by mass of emulsifier sodium dodecylbenzene sulfonate, 0.09 parts by mass of initiator benzoyl peroxide, and 210 parts by mass of distilled water were mixed, and stirred for reaction at 70°C for 7 hours. After the reaction, the mixture was washed twice with acetone and deionized water in sequence, filtered, and dried in a vacuum drying oven at 65°C for 10 hours to obtain a toughening agent.

[0024] Furthermore, the preparation steps of the pre-irradiated ethylene-vinyl acetate copolymer are as follows: the ethylene-vinyl acetate copolymer is pre-irradiated with beta rays through a 120kW electron accelerator, and the irradiation conditions are: the transmission speed is set to 4.8m / min, the acceleration voltage is 3MeV, the beam length is 7.5cm, the scanning width is 1.2m, and the irradiation dose is 10kGy to obtain the pre-irradiated ethylene-vinyl acetate copolymer.

[0025] Furthermore, the preparation method of the phenyl dichlorophosphine modified brominated epoxy resin is as follows: After mixing brominated epoxy resin, triethylamine and toluene, add dropwise a toluene solution of 66% by mass of phenyldichlorophosphine at -5°C while stirring, raise the temperature to 70°C after the addition is complete, keep the temperature for reaction for 2 hours, cool after the reaction is complete, filter out triethylamine hydrochloride, evaporate the filtrate under reduced pressure to remove the solvent and excess triethylamine, then recrystallize with acetonitrile, dry and seal for storage to obtain phenyldichlorophosphine-modified brominated epoxy resin; wherein the molar ratio of hydroxyl, triethylamine and phenyldichlorophosphine in the brominated epoxy resin is 1:0.9:1, and the mass ratio of brominated epoxy resin to toluene is 1:3.2.

[0026] Furthermore, the temperatures of each section of the twin-screw extruder are: 200°C in zone 1, 210°C in zone 2, 220°C in zone 3, 220°C in zone 4, 220°C in zone 5, 200°C in zone 6, 200°C in zone 7, 210°C in zone 8, head temperature 230°C, screw speed: 300r / min; the injection molding conditions: the temperatures of each section of the injection molding machine are: 250°C, 250°C, 250°C, 250°C, 230°C.

[0027] The flame retardant is compounded by phenyl dichlorophosphine modified brominated epoxy resin and MCA flame retardant in a mass ratio of 16:6.

[0028] The laser marking agent is obtained by mixing tin dioxide, mica, aluminum oxide, titanium dioxide and antimony pentoxide in a mass ratio of 3:5:4:2:3. Example 2

[0029] A method for preparing a modified PBT material for laser marking, the preparation steps are as follows: (1) Ingredients: Weigh and prepare the ingredients according to the following raw material components and proportions: 45 parts by mass of carboxyl-terminated PBT resin, 6 parts by mass of toughening agent, 20 parts by mass of flame retardant, 25 parts by mass of glass fiber, 0.7 parts by mass of compatibilizer, 1 part by mass of laser marking agent, 2 parts by mass of laser laser engraving masterbatch, and 0.3 parts by mass of antioxidant; (2) Pretreatment of carboxyl-terminated PBT resin: 45 parts by weight of carboxyl-terminated PBT resin, 13 parts by weight of benzyltrichloride, 0.015 parts by weight of ferric chloride, and 130 parts by weight of tetrachloromethane were mixed and stirred for 3 hours, and then heated at 72° C. for 1 hour to obtain a pretreated PBT resin; (3) Toughening agent pretreatment: 6 parts by weight of toughening agent, 2.5 parts by weight of benzyltrichloride, 0.018 parts by weight of ferric chloride, 40 parts by weight of acetone, and 70 parts by weight of tetrachloromethane were mixed and stirred for 3 hours, and then heated at 72° C. for 1 hour to obtain a pretreated toughening agent; (4) primary mixing: the pretreated toughening agent prepared in step (3), the antioxidant, 0.3 parts by mass of anhydrous aluminum chloride, and 70 parts by mass of 1,2-dichloroethane are mixed, stirred at 40° C. for 5 h, and then quenched with an ice-cold 1 mol / L HCl solution. The mixture obtained after quenching is extracted twice with dichloromethane. After extraction, it is washed twice with deionized water, a 5% sodium bicarbonate aqueous solution, and a saturated NaCl solution, and then rotary evaporated to obtain a primary mixture; (5) Secondary mixing: the primary mixture, flame retardant, 150 parts by mass of dichloromethane, 7 parts by mass of triethylamine, and 0.01 parts by mass of dimethylaminopyridine were mixed at 5°C, then heated to 25°C and stirred for 4 hours, extracted twice with dichloromethane, washed twice with deionized water, 5% sodium bicarbonate aqueous solution, and saturated NaCl solution, and then rotary evaporated to obtain a secondary mixture; (6) Tertiary mixing: The secondary mixture, the pretreated PBT resin, 15 parts by weight of aluminum chloride, and 190 parts by weight of benzene were stirred and dispersed at 1500 rpm for 20 min, then heated to 80° C. and stirred for reaction. After reacting for 2 h, the mixture was heated to 110° C. and stirred at 1500 rpm for reaction overnight until substantially no hydrogen chloride gas was generated, and then cooled to room temperature to obtain a tertiary mixture. (7) Fourth mixing: The tertiary mixture, 25 parts by weight of glass fiber, 0.7 parts by weight of a compatibilizer, 1 part by weight of a laser marking agent, and 2 parts by weight of a laser engraving masterbatch are uniformly mixed, and then blended and granulated in a twin-screw extruder. At the same time, the obtained composite material is injection molded in an injection molding machine to obtain a modified PBT material for laser marking.

[0030] Furthermore, the preparation method of the toughening agent is as follows: 60 parts by mass of pre-irradiated ethylene-vinyl acetate copolymer, 40 parts by mass of 4-vinylphenylacetic acid, 0.5 parts by mass of dispersant calcium hydroxyphosphate, 0.5 parts by mass of emulsifier sodium dodecylbenzene sulfonate, 0.12 parts by mass of initiator benzoyl peroxide, and 280 parts by mass of distilled water were mixed, and stirred for reaction at 75°C for 8 hours. After the reaction, the mixture was washed with acetone and deionized water for 3 times in sequence, filtered, and dried in a vacuum drying oven at 65°C for 11 hours to obtain a toughening agent.

[0031] Furthermore, the preparation steps of the pre-irradiated ethylene-vinyl acetate copolymer are as follows: the ethylene-vinyl acetate copolymer is pre-irradiated with beta rays through a 120kW electron accelerator, and the irradiation conditions are: the transmission speed is set to 4.8m / min, the acceleration voltage is 3MeV, the beam length is 7.5cm, the scanning width is 1.2m, and the irradiation dose is 10kGy to obtain the pre-irradiated ethylene-vinyl acetate copolymer.

[0032] Furthermore, the preparation method of the phenyl dichlorophosphine modified brominated epoxy resin is as follows: After mixing brominated epoxy resin, triethylamine and toluene, add dropwise a toluene solution of 66% by mass of phenyldichlorophosphine at -3°C while stirring, raise the temperature to 75°C after the addition is complete, and keep the temperature to react for 3 hours. After the reaction is completed, cool the mixture, filter out triethylamine hydrochloride, evaporate the filtrate under reduced pressure to remove the solvent and excess triethylamine, then recrystallize with acetonitrile, dry and seal for storage to obtain phenyldichlorophosphine-modified brominated epoxy resin; wherein the molar ratio of hydroxyl, triethylamine and phenyldichlorophosphine in the brominated epoxy resin is 1:1:1.1, and the mass ratio of brominated epoxy resin to toluene is 1:3.3.

[0033] Furthermore, the temperatures of each section of the twin-screw extruder are: 210°C for zone 1, 220°C for zone 2, 230°C for zone 3, 230°C for zone 4, 225°C for zone 5, 210°C for zone 6, 210°C for zone 7, 220°C for zone 8, head 250°C, screw speed: 300r / min; the injection molding conditions: the temperatures of each section of the injection molding machine are: 250°C, 250°C, 250°C, 250°C, 230°C.

[0034] The flame retardant is compounded by phenyl dichlorophosphine modified brominated epoxy resin and MCA flame retardant in a mass ratio of 16:7.

[0035] The laser marking agent is obtained by mixing tin dioxide, mica, aluminum oxide, titanium dioxide and antimony pentoxide in a mass ratio of 4:7:5:2.5:4. Example 3

[0036] A method for preparing a modified PBT material for laser marking, the preparation steps are as follows: (1) Ingredients: Weigh and prepare the following raw materials according to the following components and proportions: 50 parts by weight of carboxyl-terminated PBT resin, 7 parts by weight of toughening agent, 25 parts by weight of flame retardant, 30 parts by weight of glass fiber, 0.8 parts by weight of compatibilizer, 1.5 parts by weight of laser marking agent, 3 parts by weight of laser laser engraving masterbatch, and 0.4 parts by weight of antioxidant; (2) Pretreatment of carboxyl-terminated PBT resin: 50 parts by weight of carboxyl-terminated PBT resin, 15 parts by weight of benzyltrichloride, 0.02 parts by weight of ferric chloride, and 150 parts by weight of tetrachloromethane were mixed and stirred for 4 hours, and then heated at 78° C. for 1 hour to obtain a pretreated PBT resin; (3) Toughening agent pretreatment: 7 parts by weight of toughening agent, 3.5 parts by weight of benzyltrichloride, 0.021 parts by weight of ferric chloride, 50 parts by weight of acetone, and 90 parts by weight of tetrachloromethane were mixed and stirred for 4 hours, and then heated at 78°C for 1 hour to obtain a pretreated toughening agent; (4) primary mixing: the pretreated toughening agent prepared in step (3), the antioxidant, 0.4 parts by mass of anhydrous aluminum chloride, and 90 parts by mass of 1,2-dichloroethane are mixed, stirred at 40° C. for 6 h, and then quenched with an ice-cold 1 mol / L HCl solution. The mixture obtained after quenching is extracted twice with dichloromethane. After extraction, it is washed twice with deionized water, a 5% sodium bicarbonate aqueous solution, and a saturated NaCl solution, and then rotary evaporated to obtain a primary mixture; (5) Secondary mixing: the primary mixture, flame retardant, 200 parts by mass of dichloromethane, 8 parts by mass of triethylamine, and 0.01 parts by mass of dimethylaminopyridine were mixed at 5°C, then heated to 25°C and stirred for 5 hours, extracted twice with dichloromethane, washed twice with deionized water, 5% sodium bicarbonate aqueous solution, and saturated NaCl solution after extraction, and then rotary evaporated to obtain a secondary mixture; (6) Tertiary mixing: The secondary mixture, the pretreated PBT resin, 20 parts by mass of aluminum chloride, and 200 parts by mass of benzene were stirred and dispersed at 1800 rpm for 30 min, then heated to 80° C. and stirred for reaction for 2.2 h, then heated to 110° C. and stirred at 1700 rpm for reaction overnight until substantially no hydrogen chloride gas was generated, and then cooled to room temperature to obtain a tertiary mixture; (7) Fourth mixing: The tertiary mixture, 30 parts by weight of glass fiber, 0.8 parts by weight of compatibilizer, 1.5 parts by weight of laser marking agent, and 3 parts by weight of laser laser engraving masterbatch are mixed evenly, and then blended and granulated in a twin-screw extruder. At the same time, the obtained composite material is injection molded in an injection molding machine to obtain a modified PBT material for laser marking.

[0037] Furthermore, the preparation method of the toughening agent is as follows: 70 parts by mass of pre-irradiated ethylene-vinyl acetate copolymer, 50 parts by mass of 4-vinylphenylacetic acid, 0.5 parts by mass of dispersant calcium hydroxyphosphate, 0.5 parts by mass of emulsifier sodium dodecylbenzene sulfonate, 0.15 parts by mass of initiator benzoyl peroxide, and 350 parts by mass of distilled water were mixed, and stirred for reaction at 80°C for 9 hours. After the reaction, the mixture was washed with acetone and deionized water for 4 times in sequence, filtered, and dried in a vacuum drying oven at 65°C for 12 hours to obtain a toughening agent.

[0038] Furthermore, the preparation steps of the pre-irradiated ethylene-vinyl acetate copolymer are as follows: the ethylene-vinyl acetate copolymer is pre-irradiated with beta rays through a 120kW electron accelerator, and the irradiation conditions are: the transmission speed is set to 4.8m / min, the acceleration voltage is 3MeV, the beam length is 7.5cm, the scanning width is 1.2m, and the irradiation dose is 10kGy to obtain the pre-irradiated ethylene-vinyl acetate copolymer.

[0039] Furthermore, the preparation method of the phenyl dichlorophosphine modified brominated epoxy resin is as follows: After mixing brominated epoxy resin, triethylamine and toluene, add dropwise a toluene solution of 66% by mass of phenyldichlorophosphine at 0°C while stirring. After the addition is complete, heat to 80°C and keep warm for 4 hours. After the reaction is complete, cool and filter to remove triethylamine hydrochloride. Distill the filtrate under reduced pressure to remove the solvent and excess triethylamine, then recrystallize with acetonitrile, dry and seal for storage to obtain phenyldichlorophosphine-modified brominated epoxy resin; wherein the molar ratio of hydroxyl, triethylamine and phenyldichlorophosphine in the brominated epoxy resin is 1:1.1:1.2, and the mass ratio of brominated epoxy resin to toluene is 1:3.4.

[0040] Furthermore, the temperatures of each section of the twin-screw extruder are: 210°C for zone 1, 220°C for zone 2, 230°C for zone 3, 230°C for zone 4, 225°C for zone 5, 210°C for zone 6, 210°C for zone 7, 220°C for zone 8, head 250°C, screw speed: 300r / min; the injection molding conditions: the temperatures of each section of the injection molding machine are: 250°C, 250°C, 250°C, 250°C, 230°C.

[0041] The flame retardant is compounded by phenyl dichlorophosphine modified brominated epoxy resin and MCA flame retardant in a mass ratio of 16:8.

[0042] The laser marking agent is obtained by mixing tin dioxide, mica, aluminum oxide, titanium dioxide and antimony pentoxide in a mass ratio of 5:8:6:3:5.

[0043] Comparative Example 1 The difference between Comparative Example 1 and Example 2 is that PBT resin is used to prepare the modified PBT material for laser marking; the remaining steps and components are the same as those in Example 2.

[0044] Comparative Example 2 The only difference between Comparative Example 2 and Example 2 is that ethylene-vinyl acetate copolymer is used as a toughening agent; the remaining steps and components are the same as those of Example 2.

[0045] Comparative Example 3 The difference between Comparative Example 3 and Example 2 is that brominated epoxy resin and MCA flame retardant are compounded to prepare the flame retardant; the remaining steps and ingredients are the same as those in Example 2.

[0046] Comparative Example 4 The difference between Comparative Example 4 and Example 2 is that the flame retardant is only phenyl dichlorophosphine-modified brominated epoxy resin; the remaining steps and components are the same as those in Example 2.

[0047] Comparative Example 5 The difference between Comparative Example 5 and Example 2 is that the carboxyl-terminated PBT resin is not pretreated; the remaining steps and components are the same as those in Example 2.

[0048] Comparative Example 6 The only difference between Comparative Example 6 and Example 2 is that the toughening agent is not pretreated; the remaining steps and components are the same as those in Example 2.

[0049] Comparative Example 7 The difference between Comparative Example 7 and Example 2 is that the raw material components and proportions are directly weighed and then blended and granulated in a twin-screw extruder, and the obtained composite material is injection molded in an injection molding machine; the remaining steps and ingredients are the same as in Example 2.

[0050] Comparative Example 8 The difference between Comparative Example 8 and Example 2 is that the antioxidant used is antioxidant 168; the remaining steps and ingredients are the same as those of Example 2.

[0051] Effect example Antioxidation performance and laser marking effect: The modified PBT materials for laser marking prepared in the embodiment and the comparative example were laser marked by a Nd:YAG laser marking machine and exposed to sunlight for 8 hours. After exposure, the color of the laser marking was observed to be yellowish. The laser marking scanning rate was set to 3000 mm / s. Flame retardancy: Flame retardancy is tested according to the UL 94 vertical combustion method in GB / T 2408-1996; Mechanical properties: The modified PBT materials for laser marking prepared in the embodiment and the comparative example were tested according to ISO527 at a test rate of 5 mm / min to test the tensile strength; and according to ISO178 at a test rate of 2 mm / min to test the bending strength; Glow-wire temperature: The modified PBT materials for laser marking prepared in the examples and comparative examples were tested for glow-wire temperature according to IEC 60695-2-12-2000; CTI value: The modified PBT materials for laser marking prepared in the examples and comparative examples were tested according to GB / T 4207-2003 to test the CTI value.

[0052] Table 1 below shows the performance test analysis results of the modified PBT materials for laser marking prepared by Examples 1 to 3 of the present invention and Comparative Examples 1 to 8.

[0053] Table 1 Laser marking effect Glow wire temperature UL94 (1.6mm) Tensile strength (MPa) Does the laser marking color turn yellow after exposure to the sun? Example 1 The marking pattern is clear without shadow No combustion at 750℃ V-0 115 no Example 2 The marking pattern is clear without shadows No combustion at 750℃ V-0 116 no Example 3 The marking pattern is clear without shadow No combustion at 750℃ V-0 109 no Comparative Example 1 The marking pattern is clear without shadow No combustion at 750℃ V-0 97 Yellowing Comparative Example 2 The marking pattern is not clear and has shadows Ignition at 750℃ V-1 89 no Comparative Example 3 The marking pattern is clear without shadow No combustion at 750℃ V-1 82 Yellowing Comparative Example 4 The marking pattern is clear without shadow Ignition at 750℃ V-0 113 Yellowing Comparative Example 5 The marking pattern is clear without shadow No combustion at 750℃ V-0 102 Yellowing Comparative Example 6 The marking pattern is not clear and has shadows Ignition at 750℃ V-1 100 no Comparative Example 7 The marking pattern is not clear and has shadows Ignition at 750℃ V-2 59 Yellowing Comparative Example 8 The marking pattern is not clear and has shadows Ignition at 750℃ V-1 99 no From Table 1, it can be found that the laser marking effect, flame retardant property, mechanical property and antioxidant effect of the modified PBT materials for laser marking prepared in Examples 1 to 3 are good, and the material does not catch fire when the glow wire contacts the material at 750°C. Compared with Example 2, in Comparative Examples 1 and 5, the mechanical property and antioxidant property of the modified PBT materials for laser marking prepared by using carboxyl-terminated PBT resin and pretreatment are good. Compared with Example 2, in Comparative Examples 2 and 6, the laser marking effect of the modified PBT materials for laser marking prepared by using 4-vinylphenylacetic acid to modify ethylene-vinyl acetate copolymer and pretreatment are good. The marking effect, flame retardant properties and mechanical properties are good, and the material does not catch fire when the glow-wire contacts it at 750°C; Compared with Example 2, Comparative Examples 3 and 4 use phenyl dichlorophosphine-modified brominated epoxy resin and MCA flame retardant to prepare flame retardants, and the flame retardant properties and mechanical properties of the modified PBT material for laser marking are good, as well as the antioxidant effect; Compared with Example 2, Comparative Example 8 uses 2,6-dimethylphenol as an antioxidant, and the laser marking effect, flame retardant properties and mechanical properties of the modified PBT material for laser marking are good, and the material does not catch fire when the glow-wire contacts it at 750°C.

[0054] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.

Claims

1. A modified PBT material for laser marking, characterized in that: In terms of weight, the raw material components include: 40 to 50 parts by weight of terminal carboxyl PBT resin, 5 to 8 parts by weight of toughening agent, 15 to 25 parts by weight of flame retardant, 20 to 30 parts by weight of glass fiber, 0.6 to 0.8 parts by weight of compatibilizer, 0.5 to 1.5 parts by weight of laser marking agent, 1 to 3 parts by weight of laser laser engraving masterbatch, and 0.2 to 0.4 parts by weight of antioxidant.

2. The modified PBT material for laser marking according to claim 1, characterized in that: The terminal carboxyl content of the terminal carboxyl PBT resin is 20-30 mol / t.

3. The modified PBT material for laser marking according to claim 1, characterized in that: The toughening agent is obtained by modifying ethylene-vinyl acetate copolymer with 4-vinylphenylacetic acid.

4. The modified PBT material for laser marking according to claim 1, characterized in that: The flame retardant is compounded by phenyl dichlorophosphine modified brominated epoxy resin and MCA flame retardant in a mass ratio of 16:6-8.

5. The modified PBT material for laser marking according to claim 1, characterized in that: The antioxidant is 2,6-dimethylphenol.

6. A method for preparing a modified PBT material for laser marking according to any one of claims 1 to 5, characterized in that: The preparation steps are as follows: (1) Ingredients: Weigh and prepare the ingredients according to the following raw material components and proportions: 40-50 parts by weight of carboxyl-terminated PBT resin, 5-7 parts by weight of toughening agent, 15-25 parts by weight of flame retardant, 20-30 parts by weight of glass fiber, 0.6-0.8 parts by weight of compatibilizer, 0.5-1.5 parts by weight of laser marking agent, 1-3 parts by weight of laser laser engraving masterbatch, and 0.2-0.4 parts by weight of antioxidant; (2) Pretreatment of carboxyl-terminated PBT resin: 40-50 parts by weight of carboxyl-terminated PBT resin, 12-15 parts by weight of benzyltrichloride, 0.01-0.02 parts by weight of ferric chloride, and 120-150 parts by weight of tetrachloromethane were mixed and stirred for 2-4 hours, and then heated at 65-78°C for 1 hour to obtain a pretreated PBT resin; (3) Toughening agent pretreatment: 5-7 parts by weight of toughening agent, 1.5-3.5 parts by weight of benzyltrichloride, 0.015-0.021 parts by weight of ferric chloride, 20-50 parts by weight of acetone, and 50-90 parts by weight of tetrachloromethane were mixed and stirred for 2-4 hours, and then heated at 65-78°C for 1 hour to obtain a pretreated toughening agent; (4) primary mixing: the pretreated toughening agent prepared in step (3), the antioxidant, 0.2-0.4 parts by weight of anhydrous aluminum chloride, and 50-90 parts by weight of 1,2-dichloroethane are mixed, stirred at 40° C. for 4-6 hours, and then quenched with an ice-cold 1 mol / L HCl solution. The mixture obtained after quenching is extracted twice with dichloromethane. After extraction, it is washed twice with deionized water, a 5% sodium bicarbonate aqueous solution, and a saturated NaCl solution, and then rotary evaporated to obtain a primary mixture; (5) Secondary mixing: the primary mixture, flame retardant, 100-200 parts by mass of dichloromethane, 6-8 parts by mass of triethylamine, and 0.01 parts by mass of dimethylaminopyridine are mixed at 5°C, then the temperature is raised to 25°C and stirred for 3-5 hours, and the mixture is extracted twice with dichloromethane. After extraction, the mixture is washed twice with deionized water, a 5% sodium bicarbonate aqueous solution, and a saturated NaCl solution, and then rotary evaporated to obtain a secondary mixture; (6) Tertiary mixing: The secondary mixture, the pretreated PBT resin, 10-20 parts by weight of aluminum chloride, and 180-200 parts by weight of benzene are stirred and dispersed at 1200-1800 rpm for 10-30 min, then heated to 80° C., stirred and reacted for 1.8-2.2 h, then heated to 110° C., stirred and reacted at 1300-1700 rpm overnight until substantially no hydrogen chloride gas is generated, and then cooled to room temperature to obtain a tertiary mixture; (7) Fourth mixing: The tertiary mixture, 20-30 parts by weight of glass fiber, 0.6-0.8 parts by weight of compatibilizer, 0.5-1.5 parts by weight of laser marking agent, and 1-3 parts by weight of laser laser engraving masterbatch are mixed evenly, and then blended and granulated in a twin-screw extruder. At the same time, the obtained composite material is injection molded in an injection molding machine to obtain a modified PBT material for laser marking.

7. The method for preparing the modified PBT material for laser marking according to claim 6, characterized in that: The preparation method of the toughening agent is as follows: 50-70 parts by weight of pre-irradiated ethylene-vinyl acetate copolymer, 30-50 parts by weight of 4-vinylphenylacetic acid, 0.5 parts by weight of dispersant calcium hydroxyphosphate, 0.5 parts by weight of emulsifier sodium dodecylbenzene sulfonate, 0.09-0.15 parts by weight of initiator benzoyl peroxide, and 210-350 parts by weight of distilled water were mixed, stirred and reacted at 70-80° C. for 7-9 hours. After the reaction, the mixture was washed with acetone and deionized water for 2-4 times, filtered, and dried in a vacuum drying oven at 65° C. for 10-12 hours to obtain a toughening agent.

8. The method for preparing the modified PBT material for laser marking according to claim 7, characterized in that: The preparation steps of the pre-irradiated ethylene-vinyl acetate copolymer are as follows: the ethylene-vinyl acetate copolymer is pre-irradiated with beta rays through a 120kW electron accelerator, and the irradiation conditions are as follows: the transmission speed is set to 4.8m / min, the acceleration voltage is 3MeV, the beam length is 7.5cm, the scanning width is 1.2m, and the irradiation dose is 10kGy to obtain the pre-irradiated ethylene-vinyl acetate copolymer.

9. The method for preparing the modified PBT material for laser marking according to claim 6, characterized in that: The preparation method of the phenyl dichlorophosphine modified brominated epoxy resin is as follows: After mixing the brominated epoxy resin, triethylamine and toluene, add dropwise a toluene solution of 66% by mass of phenyldichlorophosphine at -5-0°C while stirring, raise the temperature to 70-80°C after the addition is complete, and keep the temperature to react for 2-4 hours. After the reaction is completed, cool the mixture, filter out triethylamine hydrochloride, evaporate the filtrate under reduced pressure to remove the solvent and excess triethylamine, then recrystallize the mixture with acetonitrile, dry it, and seal it for storage to obtain a brominated epoxy resin modified with phenyldichlorophosphine; wherein the molar ratio of hydroxyl group, triethylamine and phenyldichlorophosphine in the brominated epoxy resin is 1:0.9-1.1:1-1.2, and the mass ratio of brominated epoxy resin to toluene is 1:3.2-3.

4.

10. The method for preparing the modified PBT material for laser marking according to claim 6, characterized in that: The temperature of each section of the twin-screw extruder is as follows: zone 1 200~210℃, zone 2 210~220℃, zone 3 220~230℃, zone 4 220~230℃, zone 5 220~225℃, zone 6 200~210℃, zone 7 200~210℃, zone 8 210~220℃, die head 230~250℃, screw speed: 300r / min; The injection molding conditions: The temperature of each section of the injection molding machine is as follows: 250℃, 250℃, 250℃, 250℃, 230℃.

Citation Information

Patent Citations

  • Mastic, caulking, sealant and adhesive compositions containing photosensitive compounds and method of reducing their surface tack

    EP0010000A1

  • Flame-retardant reinforcing PBT (Polybutylece Terephthalate) composite material with excellent laser printing effect and preparation method of material

    CN107057301A

  • Flame-retardant PBT composite material used for laser marking and having high glowing wire ignition temperature, and preparation method thereof

    CN107163518A

  • Dark-color halogen-free flame-retardant PBT composite material can be used for laser marking, and preparation method thereof

    CN107353604A

  • Laser carving master batch with noctilucent effect and color identification and preparation method of laser carving master batch

    CN114196158A